Pembelajaran Matematika SD Berbasis Etnomatematika: Keliling dan Luas dalam Budaya Lokal - Enney Margaretha Situmorang; Gracia Citra Lavenia Simanungkalit; Gabriel Depany Simanjorang; Elvi Mailani; Nur Rarastika (CV. ITTC INDONESIA, 2025)
The ethnomathematics approach can also be applied through the development of interactive learning media, such as educational games based on local culture. This research aims to describe how local cultural elements are utilized in the introduction of mathematical concepts such as perimeter and area of flat buildings. This type of research is descriptive qualitative research. The subjects in this research are a number of scientific articles that discuss the application of ethnomathematics in elementary school mathematics learning. The data collection technique used in this research is documentation study. analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. After conducting research on several journals related to the application of ethnomathematics in elementary school mathematics learning, it can make a positive contribution in improving the connection of mathematical concepts with real life, understanding the concepts of geometry and flat/space building, motivation and interest in learning students, and developing innovative learning media. Based on the results of research and analysis from various journals, it can be concluded that the application of the ethnomathematics approach in learning mathematics in elementary schools makes a very positive contribution in improving the quality of learning.